2013
DOI: 10.1111/j.1532-950x.2013.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Tissue Impedance Measurement Interpretation for Correct Veress Needle Placement in Canine Cadavers

Abstract: Diagnostic accuracy of TIMI for Veress needle placement was higher than has been reported for other tests, and TIMI had a shallow learning curve. TIMI successfully detected all incorrect Veress needle placements. Further prospective evaluation of Veress needle placement with and without TIMI is warranted to determine if its use increases operator detection of inappropriate Veress needle placements or decreases installment phase complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…Neither of the articles describing these studies reported laparoscopic entry‐related complications or discussed minor complications such as gas leaks or repeated entry attempts. An older review of the veterinary literature noted that, of 36 reports in dogs and cats, only 7 reports revealed entry technique complications, with a total of 30 of 749 (4%) procedures having entry technique complications . The retrospective nature of the included reports likely severely underestimated the true rate of entry technique complications, particularly minor complications that may have seemed of low impact.…”
Section: Discussionmentioning
confidence: 99%
“…Neither of the articles describing these studies reported laparoscopic entry‐related complications or discussed minor complications such as gas leaks or repeated entry attempts. An older review of the veterinary literature noted that, of 36 reports in dogs and cats, only 7 reports revealed entry technique complications, with a total of 30 of 749 (4%) procedures having entry technique complications . The retrospective nature of the included reports likely severely underestimated the true rate of entry technique complications, particularly minor complications that may have seemed of low impact.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported that splenic laceration secondary to Veress needle placement was the most common complication associated with laparoscopy . According to Whittemore et al, maintaining sharpened trochars avoids having to apply excessive force when entering the abdomen, which in turn, minimizes the risk of inadvertent laceration to abdominal viscera . In addition, it has been previously recommend to ensure the urinary bladder is completely empty prior to surgery to reduce the risk of inadvertent damage during Veress needle and/or trocar placement.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been previously recommend to ensure the urinary bladder is completely empty prior to surgery to reduce the risk of inadvertent damage during Veress needle and/or trocar placement. It has been recommended using alternative trocar placement techniques, such as the modified Hasson or Hasson technique, to reduce the incidence of splenic laceration with abdominal entry . Furthermore, implementing open methods for pneumoperitoneum by using the Hasson technique may reduce the risk of other intraoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…We are not aware of any studies in the veterinary literature that have evaluated correct VN placement in anesthetized patients. In a dog cadaver study, the interpretations of tissue impedance measurements resulted in a 90% accuracy and 100% specificity for identification of incorrect VN placement . In another veterinary study that evaluated intercostal insertions of VN, the authors confirmed that correct intraperitoneal placement was achieved after a clear double click was heard .…”
Section: Discussionmentioning
confidence: 89%
“…Finally, for the purpose of this study, we used canine cadavers, and extrapolations of our results to living animals should be made with caution. Whittemore et al demonstrated that tissue integrity was stable for up to 40 hours after death, so we chose to use cadavers of dogs that had been dead for less than 40 hours. However, other factors associated with live animals, such as breathing and intestinal movements as well as the individual variability in intra‐abdominal topography or adhesions, could influence the VNPD.…”
Section: Discussionmentioning
confidence: 99%